Knowledge of cardiovascular disease among three-wheeler drivers in Anuradhapura police division - Gunarathne, W.G.R.; Lakshani, L.B.N.; Kamalarupan, L.; Guruparan, M. (Faculty of Allied Health Sciences, University of Jaffna, Sri Lanka, 2023)
Introduction: Cardiovascular diseases are one of the leading causes of death. Three-wheeler drivers are exposed to various risk factors which make these individuals vulnerable to cardiovascular diseases. Objective: To assess the knowledge on cardiovascular diseases (CVD) among three-wheeler drivers in the Anuradhapura police division. Methodology: A community-based descriptive cross-sectional study was done among 383 three-wheelers in the Anuradhapura police division. An interviewer-administered questionnaire was used to collect data. Data were analyzed by SPSS 25 (Statistical Package of Social Sciences). Data were analyzed in descriptive statistics.100 three-wheeler parks were selected by convenience sampling method based on the distance, among these participants were randomly selected from the list of auto drivers. Results: The age range was 23 to 75 years and the mean age was 50.07 years (SD=10.303). More than fifty percent (51.2%) had an average knowledge of CVDs. The average score of the knowledge was recorded as 68.029 (SD= 11.489). The majority of the participants understood “heart disease” as a blockage in the heart (97.1%) and they only knew the heart is an organ affected by CVDs (96.3%). Only 22.2% identified pain on the left side chest & arm as the symptom of a heart attack. Most of the participants (81.2%) were aware high blood sugar can cause heart disease. The majority of the participants (92.2%) knew that sudden death may occur due to CVD, whereas none of them was aware kidney failure also can occur due to CVDs. The risk factors of CVD identified by many of them were: Smoking (98,2%, oily foods (98.2%), sitting a long time per day (97.4%), Increased salt intake (83.8%), obesity (95.3%), work-related stress (82.2%), sleeping disturbance (85.1%), high blood sugar (86.4%), and high blood pressure (90.9 %). However, almost all of them (99%) were not aware of alcohol, also one of the risk factors. Conclusion: Nearly half of the participants (48.8%) had poor knowledge on cardiovascular diseases. Conduction awareness programme on cardiovascular risk factors, especially hazardous effects of consumption of alcohol is mandatory.
Keywords: Cardiovascular diseases; Heart diseases; Three-wheeler drivers; Risk factors